2006
DOI: 10.1177/003335490612100612
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Childhood Asthma and Community Violence, Los Angeles County, 2000

Abstract: Community violence as measured by the rate of assault hospi; talizations is associated with childhood asthma in Los Angeles County. Health care providers should consider their asthmatic patients' social environments when devising treatment plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…Various studies in the last decade, the majority of which in the United States, identified an association between community violence and asthma 8,9,10,11,12,20 . Although the studies analyzed different outcomes, like hospitalizations and occurrence and number of days with symptoms, besides distinct contexts, they showed a similar association to that found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies in the last decade, the majority of which in the United States, identified an association between community violence and asthma 8,9,10,11,12,20 . Although the studies analyzed different outcomes, like hospitalizations and occurrence and number of days with symptoms, besides distinct contexts, they showed a similar association to that found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the independent variable "community violence" was not measured directly with a specific instrument. The majority of the studies on the theme have found that exposure to a violent act such as being assaulted or witnessing a fight involving firearms or knives is already representative of the community violence phenomenon 8,9,10,11,12,20 . When the SCAALA project was designed, there were no validated indicators for measuring this phenomenon in the Brazilian population, or for Table 2 Logistic regression between items on community violence and presence of asthma symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] Studies on youth in urban settings have found links between mental health, exposure to violence, and asthma morbidity or hospitalization. 4,[6][7][8] One recent researcher also found a synergistic effect between traffic-related air pollution and asthma among children that were exposed to violence in an urban setting. 9 Some existing researchers have indicated that exposures to interpersonal or domestic violence are likely important risk factors for asthma episodes for both children and adults.…”
Section: Introductionmentioning
confidence: 98%